Ultrasound attenuation estimation using backscattered echoes from multiple sources - Bigelow, Timothy A. (Acoustical Society of America, 2008)
The objective of this study was to devise an algorithm that can accurately estimate the attenuation along the propagation path (i.e., the total attenuation) from backscattered echoes. It was shown that the downshift in the center frequency of the backscattered ultrasound echoes compared to echoes obtained in a water bath was calculated to have the form Δf=mf(o)+b after normalizing with respect to the source bandwidth where m depends on the correlation length, b depends on the total attenuation, and f(o) is the center frequency of the source as measured from a reference echo. Therefore, the total attenuation can be determined independent of the scatterer correlation length by measuring the downshift in center frequency from multiple sources (i.e., different f(o)) and fitting a line to the measured shifts versus f(o). The intercept of the line gives the total attenuation along the propagation path. The calculations were verified using computer simulations of five spherically focused sources with 50% bandwidths and center frequencies of 6, 8, 10, 12, and 14 MHz. The simulated tissue had Gaussian scattering structures with effective radii of 25 μm placed at a density of 250∕mm(3). The attenuation of the tissue was varied from 0.1 to 0.9 dB∕cm-MHz. The error in the attenuation along the propagation path ranged from −3.5±14.7% for a tissue attenuation of 0.1 dB∕cm-MHz to −7.0±3.1% for a tissue attenuation of 0.9 dB∕cm-MHz demonstrating that the attenuation along the propagation path could be accurately determined using backscattered echoes from multiple sources using the derived algorithm.